Socio-psychological technologies of occupational health formation of specialists in economics - Burlakova, Iryna; Yevdokymova, Natalia; Sheviakov, Oleksii; Kakhno, Iryna; Ponomarenko, Viktoriia (International Journal of Psychosocial Rehabilitation, 2020)
It is revealed that a person’s success in professional activity is closely related to his health, and the impact of health on his career and vice versa is an interdependent process. It is proved that healthy behaviour is a concrete manifestation of the psychological potential of health, it is both a process and the result of the interaction of such factors as motivation to health; lessons learned in maintaining health; the ability to maintain your health at an attained level. For the usage of the appropriate socio-psychological technologies for the formation of occupational health of the economic sphere professionals, we considered the factors of a three-component structure that combines cognitive, emotional and behavioural modules. The cognitive module provides an adequate understanding of the specialist about his level of health. Emotional module includes the full range of «health / illness» experiences arising from a specialist involved in a particular professional situation. The behavioural module reflects the behaviour of a specialist, which facilitates adaptation to changing environmental conditions and professional activity. We also refer to the psychological factors of occupational health of the economic sphere professionals as stressors of professional activity and individual-psychological features of the personality of a professional. The main stressors that affect the activities of the economic sphere professionals are the following: the content of professional activity, its organization; professional career; corporate relationships; non-organizational sources of stress. The impact of various stress factors on the occupational health of the economic sphere specialist is great. The main features of this negative impact are: negative self-esteem; feelings of guilt; increasing aggression, hostility; feeling of emotional exhaustion; presence of psychosomatic disease. In terms of satisfaction with life and happiness, it depends on four factors: emotional equilibrium; life priorities; work and rest ratio; own weight. Most of the described factors can be attributed to the objective influences and subjective experience of the situation in professional activity and based on the level of development of psychological resources of specialists in the economic sphere.